Effect of stress relaxation on globe-cone seal performance with a gasket. (October 2019) - Wang, Li-Na; Sun, Heng-Chao; Qi, Lei; Sun, Wei; Zhao, Yue-Shuai; Sun, Li-Chen; Meng, Dong-Hui
Abstract: The globe-cone seal is widely used in pipeline joint of satellite propulsion system, and the seal performance has prominent influence on the safety of satellite in orbit. In fact, the leakage problem of globe-cone seal is generally solved by adding a gasket between the globe and cone, but so far there is no correlative research to explain the above phenomena. In addition, it is necessary to consider the effect of stress relaxation on the globe-cone seal performance, especially after a long-term storage or working in orbit. Based on this, a finite element model (FEM) of globe-cone seal with a gasket is established under considering the stress relaxation. Then the variation of the nut residual preload force, the contact stresses cone/gasket and globe/gasket with the increasing creep time is obtained under different working parameters. Then the leakage rate formula of globe-cone seal is obtained under considering the stress relaxation effect by derivation of formulas. The leakage rate variation of the globe-cone seal with a gasket under considering stress relaxation effect is obtained with increasing creep time. The performance analysis of globe-cone seal with a gasket is carried out under considering the stress relaxation in the paper. Highlights: The performance of globe-cone seal with a gasket has prominent influence on the safety of satellite in orbit. It is necessary to consider the effect of stress relaxation on globe-cone seal performance, especially a long-term working. A finite element model of globe-cone seal with a gasket is established under considering the stress relaxation. Variation of the nut residual preload force, the contact stresses with the increasing creep time is obtained. Leakage rate variation of globe-cone seal under considering stress relaxation effect is obtained with increasing creep time.